Estudio documental sistemático sobre las tecnologías blockchain y su aplicación a la ciberseguridad 2024 - Molina Gavidia, Marco Vinicio (2024)
Blockchain is a decentralized technology that emerged from the publication of the book "Bitcoin: A Peer-to-Peer Electronic Cash System" (Nakamoto, 2008), or in Spanish "Un Sistema de Efectivo Electrónico Usuario-a-Usuario." Although this technology is frequently associated with Bitcoin, this article is based on an in-depth analysis of Blockchain technology and its impact in various areas, especially in the field of cybersecurity. The blockchain, also known as a block chain, stores operations in interconnected blocks, guaranteeing the security and integrity of information by providing an additional layer of security through decentralized data storage and verification, significantly reducing the risk of cyber attacks. In terms of cybersecurity, given the significant threat posed by online exposure of personal information and the notable degree of scams on the internet in various contexts, one of the benefits of this technology is its ability to verify the authenticity of transactions in real time. Therefore, the current project "Systematic Documentary Study on Blockchain Technologies and Their Application to Cybersecurity 2024" aims to highlight the unique characteristics of Blockchain technology, such as immutability, transparency, decentralization, and its use to strengthen cybersecurity by allowing data protection, secure, and robust authentication.